Physical and performance profiles differentiate competitive levels in U-18 basketball players - Goniotaki, A.; Bourdas, D. I.; Travlos, A. K.; Bakirtzoglou, P.; Theos, A.; Zacharakis, E. (Sports, 2026)
Background: Evidence on how physical and technical factors distinguish U-18 basketball levels is limited, yet these determinants may aid talent identification and development. This study examined differences in anthropometric, physical performance, and technical characteristics between high-level (HL; n = 38) and low-level (LL; n = 35) U-18 male basketball players and explored relationships between technical skills and key physical attributes across all participants. Methods: Participants were evaluated across anthropometry, physical performance, and basketball-specific technical skills. Statistical analyses assessed between-group differences and correlations, with significance set at p <= 0.05. Results: Compared to LL players, HL players exhibited significantly superior physical attributes, including greater height (Cohen`s d = 0.67) and arm-span (d = 0.65), reduced body fat (d = -0.58), and advanced performance metrics (10 m-speed running (d = -0.78), 20 m-speed running (d = -0.93), flexibility (d = 1.26), counter-movement jump height (d = 1.27), intermittent endurance (d = 1.18)). Technical proficiency in tasks such as 10 m- and 20 m-speed dribbling, maneuver dribbling and defensive sliding was also significantly faster in the HL group (d = -0.96, d = -1.05, d = -1.87, and d = -1.14, respectively). Several anthropometric and performance variables were strongly correlated with technical skills, indicating their relevance for distinguishing competitive levels. Conclusions: These findings underscore the interplay of physical, technical, and performance factors in high-level youth basketball. Coaches may use this information to guide targeted training strategies that support talent identification, player development, and competitive success.